Genetic signatures through space, time and multiple disturbances in a ubiquitous brooding coral - Underwood, J.; Richards, Zoe; Miller, K.; Puotinen, M.; Gilmour, J. (Wiley-Blackwell Publishing, 2018)
The predominance of self-recruitment in many reef-building corals has fundamental and complex consequences for their genetic diversity, population persistence and responses to climate change. Knowledge of genetic structure over local scales needs to be placed within a broad spatial context, and also integrated with genetic monitoring through time to disentangle these consequences. Here, we examined patterns of genetic diversity over multiple spatio-temporal scales across tropical Australia in the ubiquitous brooding coral, Seriatopora hystrix. We also analysed complimentary environmental and demographic data to elucidate the seascape drivers of these patterns. Large genetic differences were detected between the east vs. west coasts of Australia. In northwest Australia, geographic differentiation dominated genetic structure over multiple scales. However, three sympatric lineages were detected at the largest offshore reef system (Scott Reef). Similar to the differences observed among putative species in eastern Australia, these lineages were associated with different levels of wave exposure. Local genetic structure within the Scott Reef system was relatively stable over 10Â years, but temporal differences were observed that reflected small but important genetic changes over a few generations during recovery after severe bleaching. These results highlight the importance of self-recruitment together with occasional longer distance connectivity for the persistence of a metapopulation across spatially and temporally variable environments. Our multidimensional research provides a foundation for further long-term genetic monitoring to inform conservation strategies and highlights that sampling scales, ecological effects and cryptic diversity are important considerations to develop realistic understanding of the evolutionary resilience of corals.